2005
DOI: 10.5194/aab-48-612-2005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of breed, sex and diet and their interactions on carcass composition and tissue weight distribution of broiler chickens

Abstract: Effects of breed, sex and diet and their interactions on carcass composition and tissue weight distribution of broiler chickens AbstractThe effects of breed (Hubbard and Anak), sex and diet (two levels of protein (high or low) with two levels of crude fiber (low or high) at each level of protein) on carcass composition and distribution of tissues over the carcass were studied. Carcass composition and ratios of muscle: bone, muscle: fat and meat: bone in the carcass did not differ significantly between breed gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
27
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 19 publications
9
27
0
1
Order By: Relevance
“…Among numerous non-genetic factors, the most important role plays broiler nutrition. Raw materials used in the feed mixture, their characteristic chemical composition, protein and mineral elements content and energy value of formulated doses, affect chemical composition of the muscle tissue (Shahin & Abd Elazeem, 2005Łukasiewicz, 2012Łukasiewicz, , Sirirat et al, 2012. In recent years many authors have also paid attention to the rearing of broilers, as a particularly important factor influencing quality traits of meat (Castelini, 2005, Ponte, 2008, Meluzzi et al, 2009, Bogosavljević-Bošković et al, 2012Nawalny, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Among numerous non-genetic factors, the most important role plays broiler nutrition. Raw materials used in the feed mixture, their characteristic chemical composition, protein and mineral elements content and energy value of formulated doses, affect chemical composition of the muscle tissue (Shahin & Abd Elazeem, 2005Łukasiewicz, 2012Łukasiewicz, , Sirirat et al, 2012. In recent years many authors have also paid attention to the rearing of broilers, as a particularly important factor influencing quality traits of meat (Castelini, 2005, Ponte, 2008, Meluzzi et al, 2009, Bogosavljević-Bošković et al, 2012Nawalny, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Consumers also appreciate chicken meat due to low price, convenient portions and freedom from religious taboos (Jaturasitha et al, 2004). Genotype (breed and strain) plays a major role in carcass characteristics and meat quality (Jaturasitha et al, 2004;Shahin et al, 2005;Chaosap et al, 2006). Despite the abundant availability of cross breed broiler strains, a A study was conducted to know the ratio of giblets on live weight and carcass weight basis of various indigenous chicken breeds.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, significant genotype x sex interaction effect on live weight and body linear measurements in broiler breeds were reported in another work [10]. In addition, significant sex x diet interactions on carcass fat and boneless carcass (meat) were documented by some authors [4].…”
Section: Introductionmentioning
confidence: 87%
“…In addition, the meat is rich in proteins, vitamins, essential amino acids, saturated fatty acids and phospholipids [3]. Previous studies had observed significant sex effect on live weight of broilers [4], of quails [5] and carcass traits [4,6,7,8] in broilers. While separate effect of sex on live weight of poultry species had been widely reported in literature, the interaction of sex with other vital factors affecting birds' productivity is rare in the literature.…”
Section: Introductionmentioning
confidence: 99%